1, 8-Naphthalimide-based fluorescent chemosensors: recent advances and perspectives. Issue 39 (25th September 2020) - Dong, Hong-Qiang; Wei, Tai-Bao; Ma, Xiao-Qiang; Yang, Qing-Yu; Zhang, Yun-Fei; Sun, Yu-Jiao; Shi, Bing-Bing; Yao, Hong; Zhang, You-Ming; Lin, Qi
Abstract : Application of the classic fluorescent dye 1, 8-naphthalimide. Abstract : 1, 8-Naphthalimide, as one of the classical dyes and fluorophores, has been widely used in analytical chemistry, materials chemistry, and biochemistry fields because of its excellent characteristic photostability, good structural flexibility, high fluorescence quantum yield, and large Stokes shift. This review mainly focuses on 1, 8-naphthalimide and its derivatives in ion detection, molecular recognition, material applications, and bioimaging in the past five years. Simultaneously, we hope to develop more powerful fluorescent chemosensors for broad and exciting applications in the future.